ANALISIS TANTANGAN DAN DAMPAK LARANGAN EKSPOR CPO TERHADAP PERDAGANGAN INTERNASIONAL DI TENGAH GUGATAN UNI EROPA DI WTO - Natasya Batara; Az Zahra, Keisha Liviya; Widiana, Vina (Investama : Jurnal Ekonomi dan Bisnis, 2024)
Currently, Indonesia has land area and quality of palm oil that is able to compete with foreign countries, making Indonesia the largest producer of palm oil in the world. Palm oil (CPO) has become a source of foreign exchange for the country through non-oil and gas export activities, this has caused many foreign countries, one of which is the European Union, to provide policies so that renewable energy production increases so that Indonesian palm oil consumers experience a decline. In reality, there are still many countries that need palm oil for industry or daily life and renewable energy production is still experiencing development in the sales process. This writing was written using a qualitative approach which was motivated by the policy made by the European Union to reduce palm oil exports in Indonesia and how Indonesia looked for opportunities, there were challenges and impacts provided by this policy. Based on research results, approximately half of the world's palm oil supply is supplied from Indonesia, but Indonesia has still received a lot of pressure since 2015 to limit palm oil exports due to policies imposed by the European Union. The RED II policy that limits palm oil exports could have a negative impact on performance, GDP, trade balance and employment in Indonesia. The palm oil industry also plays a significant role in creating employment opportunities, so that the policies provided by the EU could threaten economic stability and employment in Indonesia. In conclusion, Indonesia needs to respond wisely to these pressures and find solutions that take into account the multidimensional impact on various economic sectors.